Perfil epidemiológico de neoplasias epiteliales de glándulas salivales - Campolo González, Andrés; Ramirez Skinner, Hernán; Vargas Díaz, Alex; León Ramírez, Augusto; Goñi Espíldora, Ignacio; Solar González, Antonieta (Revista Médica de Chile, 2018)
Background: Epithelial tumors of the salivary glands, including benign tumors and aggressive malignancies with different prognoses, are uncommon. Aim: To describe the frequency and distribution of salivary gland tumors according to age, gender and anatomical location. Material and methods: Review of pathological reports of salivary gland tumors of a Pathology laboratory at a clinical hospital from 2006 to 2016. Results: Five hundred ninety salivary gland biopsies were reviewed. Of these, 286 (49%) were primary epithelial tumors of the salivary glands. Two hundred thirty (80%) were benign and 56 (20%) were malignant tumors. Regarding location, 274 (96%) were in the major salivary glands, and 12 (4%) in the minor salivary glands. The most common histological types were pleomorphic adenoma for benign tumors in 172 cases, followed by papillary cystadenoma lymphomatosum in 33 cases. Mucoepidermoid carcinoma was the most common malignant tumor in 14 cases. Conclusions: These results are similar to reports from abroad, however more studies are necessary to be able to establish a more representative and updated analysis.